Identification and Intraspecific Typing of Plague Microbe Strains with Their Potential Virulence Determination Using PCR - A. V. Gaeva; E. G. Boolgakova; I. Yu. Sukhonosov; L. V. Anisimova; L. A. Novichkova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2011)
Developed is the method of identification and intraspecific typing of plague microbe strains along with their potential virulence determination. Intraspecific differentiation and focal attribution of the examined plague microbe strains can be determined by monolocus VNTR-PCR, and main virulence determinants (chromosomal pigmentation region and calcium-dependence plasmid genes) - by multiplex PCR.